PENGARUH LAMA KONTAK DAN KERAPATAN TANAMAN ECENG GONDOK DALAM MEREDUKSI KADMIUM PADA AIR LARUTAN PUPUK BUATAN - Nugroho, Aldo Arta; Wahyuningsih, Nur Endah; Ginandjar, Praba (Jurnal Kesehatan Masyarakat (e-Journal), 2019)
Preliminary test results showed that irrigation water of shallot in Brebes contains cadmium on average 0.028 mg/l which has exceeded the quality standard in the Government Regulation of the Republic of Indonesia that is 0.01 mg/l. One method used to reduce cadmium levels is phytoremediation using water hyacinth plants. The purpose of this study was to analyze the effect of phytoremediation of water hyacinth plants with density variations in plant (8 individuals/m2, 15 individuals/m2 and 22 individuals/m2) and contact time (3 days and 6 days) to cadmium levels in fertilizer solutions. This study used quasi-experimental design with a non equivalent control group. The sample used is an artificial fertilizer solution. The sample of this study was 160 liters for 8 treatments with 4 repetitions. Methods to test cadmium levels used the Atomic Absorption Spectrophotomete (AAS). The data analysis used was the Friedmann test with a confidence level of 95%. The highest cadmium level decrease was found in density variations in plant of 22 individuals/m2 and 6 days of contact time of 0.061 mg / l (112.96%). Based on the Friedmann test p value = 0,0001 (p <0.05) so it noted that there are differences and with the Mann Whitney test that is known that there are no significant difference between the treatment of 8 individuals/m2 with 15 individuals/m2 and 15 individuals/m2 with 22 individuals/m2, but there are significant difference between 8 individuals/m2 with 22 individuals/m2. The conclusion of this study is water hyacinth plants with density variations in plant and contact time can reduce cadmium levels in fertilizer solutions on average of 67.205% and have been able to reduce cadmium levels to the specified quality standard which is <0.01 mg/l.